2010
DOI: 10.4306/pi.2010.7.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use during Pregnancy and Related Risk Factors in Korea

Abstract: ObjectiveThe number of Korean women of childbearing age who drink alcohol and binge drink has increased remarkably in recent years. In the present study, we examined self-reported rates of alcohol use before and during pregnancy and identified maternal characteristics associated with drinking in pregnancy.MethodsOne thousand pregnant Korean women who visited the Department of Obstetrics and Gynecology (OB/GYN) completed a self-administered questionnaire that sought information on their demographic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 10 publications
6
21
4
1
Order By: Relevance
“…Ceccanti and colleagues (2007) conducted similar work in Italy in order to more fully understand the Italian phenotype of FASD and the drinking habits of Italian women for the purposes of better targeting mechanisms for prevention and intervention. In Korea, Lee and colleagues (2010) also investigated prevalence of drinking during pregnancy and related risk factors specific to their population. Systematic investigation of cultural variables is key for successfully generalizing research on FASD.…”
Section: Addressing Cultural Barriers To Implementationmentioning
confidence: 99%
“…Ceccanti and colleagues (2007) conducted similar work in Italy in order to more fully understand the Italian phenotype of FASD and the drinking habits of Italian women for the purposes of better targeting mechanisms for prevention and intervention. In Korea, Lee and colleagues (2010) also investigated prevalence of drinking during pregnancy and related risk factors specific to their population. Systematic investigation of cultural variables is key for successfully generalizing research on FASD.…”
Section: Addressing Cultural Barriers To Implementationmentioning
confidence: 99%
“…27 In addition to the absence of a steady partner, other maternal risk factors commonly associated with alcohol abuse are: aged over 30 years, low education, "non-white" skin color, use of tobacco and illicit drugs, as well as socio-economic vulnerability. 16,25,26,28 A recent review showed that women who are older, have lower education, are unmarried, unemployed, with lower stature, lower body mass index, nutritional status considered suboptimal, mental health problems, who suffered sexual abuse, who had fewer prenatal consultations, who are smokers, drug users and who have partners who also consumed alcohol are at increased risk of having a child with FASD. 1 In São Paulo city, research carried out by Mesquita and Segre 10 identified 31.1% of the postpartum women as positive T-ACE.…”
Section: Variables Negative T-ace Positive T-ace P (N=758) (N=60)mentioning
confidence: 99%
“…According to the National Health and Nutrition Examination Survey by Korea Centers for Disease Control and Prevention (2013), the lifetime prevalence rate of smoking in men aged 30-39 years was 75%, and current smoking rate was 54.8%, while 55.3% of women aged 19-29 years were exposed to ETS. Lee et al (2010) reported 16.4% maternal alcohol consumption during pregnancy in a sample of 1000 people. In our study also, 12.1% of pregnancies had maternal alcohol consumption.…”
Section: Discussionmentioning
confidence: 96%